Seeking environmentally sustainable solutions for inland aquaculture in Bangladesh - Konstancja Woźniacka; Lisa K. Bickley; Richard D. Heal; Ilya M.D. Maclean; Neaz A. Hasan; Mohammad Mahfujul Haque; Grant D. Stentiford; Regan Early; Michelle Devlin; Charles R. Tyler (Environmental Challenges)
Inland fresh- and brackish aquaculture is a key component of global food security, however, its rapid growth has impacted adversely on the environment. The future growth of the aquaculture industry will need to balance food production more effectively against the exploitation of natural resources. This review considers the case for inland aquaculture in Bangladesh – currently the world's fifth-biggest inland aquaculture producer with nearly 3 million tonnes of aquaculture production (2022). Current practices associated with different forms of inland aquaculture in the country are outlined, with their associated demands on the environment highlighted. Future projections for aquaculture expansion are assessed for their potential to impact on and be limited by the availability and quality of natural resources, including freshwater, and concerns for its contamination and salinisation. The effects of land use changes, exploitation of wild populations, introduction of invasive species, and spread of diseases on potential production are also examined. The paper addresses how these challenges may be met, both for achieving production aspirations and for limiting impact on nature. The review offers a viewpoint on potential collective actions for sustainable aquaculture, aligned with Bangladesh's socioeconomic characteristics, and in collaboration with in-country partners. To achieve the projected 14% increase in production by 2025, Bangladesh's aquaculture sector must balance growth with the effective management of finite freshwater and land resources. Key recommendations include prioritising adaptations by farmers for sustainable intensification of their production and facing changing climate impacts. Aquaculture policy needs to support the provisioning of the necessary knowledge, tools, and adequate resources to enable farmers to implement resource-efficient management strategies.